2008
DOI: 10.1088/0031-9155/53/23/017
|View full text |Cite
|
Sign up to set email alerts
|

Low density contrast agents for x-ray phase contrast imaging: the use of ambient air for x-ray angiography of excised murine liver tissue

Abstract: We report a new preparative method for providing contrast through reduction in electron density that is uniquely suited for propagation-based differential x-ray phase contrast imaging. The method, which results in an air or fluid filled vasculature, makes possible visualization of the smallest microvessels, roughly down to 15 microm, in an excised murine liver, while preserving the tissue for subsequent histological workup. We show the utility of spatial frequency filtering for increasing the visibility of min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…This phenomenon is successfully used in demonstrating air penetration into the neonate rabbit lung. 89 There is interest in using air 90,91 and carbon dioxide 92 gases as intravascular contrast agents to achieve microangiographic phase-contrast imaging because these gases transiently fill vessels, creating a refractive index gradient. However, in small animals, vascular imaging only can be achieved when vessels are completely filled with gas.…”
Section: Other Sr Techniques and Simultaneous Multi-sr Imaging Approamentioning
confidence: 99%
“…This phenomenon is successfully used in demonstrating air penetration into the neonate rabbit lung. 89 There is interest in using air 90,91 and carbon dioxide 92 gases as intravascular contrast agents to achieve microangiographic phase-contrast imaging because these gases transiently fill vessels, creating a refractive index gradient. However, in small animals, vascular imaging only can be achieved when vessels are completely filled with gas.…”
Section: Other Sr Techniques and Simultaneous Multi-sr Imaging Approamentioning
confidence: 99%
“…The liver was prepared by fixation in a formaldehyde solution for approximately three days at room temperature followed by dehydration in room air to roughly 80% of its original weight, as described in Ref. 13. The venous structure shows strong phase contrast features owing to the presence of ambient air within the vessels.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that XPC imaging techniques have excellent potential for many medical applications (Lewis, 2004; Donath, et al, 2010). For example, XPC angiography may offer improved visualization of blood vessel structure without the need for contrast agents based on heavy elements, a major risk factor associated with conventional contrast agent angiography (Momose, et al, 2000; Takeda, et al, 2002; Laperle, et al, 2008). XPC imaging has also been shown to improve the visualization of cartilage and to detect early degenerative changes after damage or disease, a task not possible with conventional radiography (Mollenhauer, et al, 2002; Majumdar, et al, 2004).…”
Section: Introductionmentioning
confidence: 99%